HAND OSTEOARTHROSIS: ON THE QUALITY OF LIFE AND AESTHETIC DISCOMFORT - Anastasia Viktorovna Sarapulova; O V Teplyakova; O B Balueva (Научно-практическая ревматология, 2013)
Osteoarthrosis (OA) is one of the most common causes of hand pains, leading to lower quality of life (QL). In addition to pain and functional impairment, the patients' aesthetic dissatisfaction that cannot be now determined or measuredis of prime importanceObjective: to assess a number of QL aspects and to measure the level of aesthetic discomfort in patients with hand OA.Subjects and methods. Sixty women aged 45–75 years with hand OA were included. The number of painful and deformed joints was determined and functional impairments were evaluated using the AUSCAN questionnaire. The patients filled out the questionnaire to determine the level of dissatisfaction with the appearance of their hands; the Ellis stress test for irrational beliefs was carried out.Results. The patients with hand OA were found to have significant aesthetic discomfort comparable with level of joint pain. Deformity phobia in the future and external discomfort because of hand deformity were most pronounced; a wish for surgical correction was less pronounced. Comparison of the results obtained in different age groups determined the highest levels of anxiety and wish for surgical correction in younger women. The patients' aesthetic dissatisfaction was also influenced by employment and internet usage.Conclusion. Aesthetic discomfort is an important component of lower QL in patients with hand OA. Further investigation of this factor and elaboration of criteria for its estimation are needed.